Analisis faktor yang berhubungan dengan kepemilikan jamban keluarga di Kampung Wainlabat Kabupaten Sorong Papua Barat - Irawati Irawati; Jenni Lilis Siagian (STIKES Karya Husada Kediri, 2022)
Community Based Total Sanitation (STBM) Stop Open Defecation is a condition when every individual in a community no longer performs open defecation behavior that has the potential to spread disease. Wailabat village with very low stbm, especially access to latrines. This study aims to analyze the relationship between the characteristics of the head of the family (education, occupation and income), latrine use behavior (knowledge and attitudes) with family latrine ownership in Wainlabat Village, Sorong Regency. This study uses an analytical survey method with a cross sectional approach. The population and sample in this study are all 42 families in Wainlabat Village, the sampling method is total sampling. Data analysis in this study used univariate analysis and bivariate analysis using chi-square test. The results showed that there was a significant relationship between education variables (p=0.00), income (p=0.015), knowledge (p=0.013) and attitudes (p=0.036) with latrine ownership. And there is no relationship with the employment variable (p=0.131) with latrine ownership. The conclusion of the study is that there is a relationship between education, income, knowledge and attitudes, but there is no relationship between work and latrine ownership. Suggestions for health workers in Wainlabat village to be more active in STBM socialization, especially on the latrine pillar